An Approach to Interface Terminology: The Example of Environmental Economics in English as a Foreign Language - Resche, Catherine (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2000)
AbstractInterface terminology will increasingly become a challenge for anyone working in disciplines that lie at the crossroads of several fields. Indeed, sciences continue to evolve, broaden their scope and, hence, borrow from one another. This study raises the problem of defining the boundaries of what constitutes an interface, and then studies the conditions for the selection of relevant terms. After reviewing some theoretical aspects of terminology science and calling for a more flexible approach, it examines some practical questions through the case of environmental economics. The target public-consisting of second-year French university students of economics-provides the opportunity to stress the need for the teacher to adapt the selection of interface terms to the situation. The conclusion, i.e. that there is no such thing as a ready-made stock of interface terms, could also be applied to translators, interpreters, terminologists and other potential users of such terminology.